FACEBOOK, THE IMAGE, AND THE VIRTUAL CEDAR BAR. - Conner, Jill (Afterimage)
The article offers information on social networking website Facebook and its impact on the art community and the concept of image. The author believes that as Facebook becomes the new agora for artists, curators, and critics, the role of the image becomes more complex. Facebook functions as an alternative to the physical, solid, and urban environment of the city. The author argues that Facebook's use of thumbnails has raised the significance of the image in a totally different way.